2018
DOI: 10.1186/s12905-018-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dysmenorrhea and predictors of its pain intensity among Palestinian female university students

Abstract: BackgroundFew studies on gynaecological problems of young females in Arab countries were published. The aim of this study was to determine the prevalence of dysmenorrhea and predictors of its pain among university students in Palestine.MethodsA cross – sectional study was carried out on a randomly selected sample of An-Najah National University female students. A pre-designed questionnaire, which included questions regarding menstrual cycle, pain during menstruation, life style, nutritional habits, and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
111
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 37 publications
23
111
1
13
Order By: Relevance
“…Di Cintio et al [26] reported that women with dysmenorrhea consumed eggs more frequently than healthy controls, but Balbi et al [27] reported that women with dysmenorrhea consumed significantly less eggs compared to healthy controls. Other studies did not find significant results concerning the association between dysmenorrhea and the consumption of meat and its alternatives [16,26,27,39,52,55].…”
Section: The Results Of the Selected Studies According To The Dietarymentioning
confidence: 92%
See 4 more Smart Citations
“…Di Cintio et al [26] reported that women with dysmenorrhea consumed eggs more frequently than healthy controls, but Balbi et al [27] reported that women with dysmenorrhea consumed significantly less eggs compared to healthy controls. Other studies did not find significant results concerning the association between dysmenorrhea and the consumption of meat and its alternatives [16,26,27,39,52,55].…”
Section: The Results Of the Selected Studies According To The Dietarymentioning
confidence: 92%
“…It developed a significantly higher risk of dysmenorrhea in women consuming excessive amount of sugar [6,29,60]. Inconsistently, Tavallaee et al [16], Grandi et al [44], Mohamadirizi and Kordi [52], Abu Helwa et al [55] found no association between the intake of sugar and dysmenorrhea. B) Fats: Fat consumption was reported by 2 studies.…”
Section: The Results Of the Selected Studies According To The Dietarymentioning
confidence: 97%
See 3 more Smart Citations